A Study on Continuous and Divided Flows for Optimal and Sustainable Dam Discharge Considering Dead Storage - Eddy Priyanto,; Siti Nazahiyah Rahmat, (International Journal of Integrated Engineering, 2025)
This study focuses on discharge optimisation for the Gredek reservoir in Gresik. East Java, Indonesia, with a specific focus on the discharge at dead storage. The primary goal was to design and analyse a suitable model for optimising the final discharge. The methodology employed simple linear equations using general variables, namely inflow  (Qin) and outflow (Qout), within a discharge balance equation, supplemented by the discharge at dead storage (QDS). This approach aimed to achieve an optimal and sustainable remaining monthly discharge (Qdiff). Based on the analysis, it was concluded that for determining Qdiff by considering inflow, outflow, and QDS, optimisation models using Continuous Flow (CF) and Divided Average (DA) approaches were successfully developed. In simulations using a 5 cm level (QDS5) at Dead Storage, the CF model yielded Qdiff values ranging from 767 m3 to 66,649 m3 at the end of each month, while the DA model yielded Qdiff values ranging from 2,568 m3 to 46,242 m3 throughout the 2021-2035 period. A comparative analysis of the CF and DA models reveals that both have distinct advantages. While the CF model achieved the highest Qdiff at 66,649 m3, the DA model's highest Qdiff was 46,242 m3. However, for comprehensive reservoir equilibrium management, a combination of both models is highly effective. The CF model is well-suited for long-term planning. While the DA model is ideal for day-to-day or monthly reservoir operational management, the CF model, in essence, estimates the potential magnitude of available water, whereas the DA model details how that water interacts with other operational components. These two models are complementary; their applicability depends entirely on the required level of detail and the scale of planning or operations.